Pyridine-based functionalized graphene oxides as a new class of corrosion inhibitors for mild steel: An experimental and DFT approach - Gupta, Rajeev Kumar; Malviya, Manisha; Verma, Chandrabhan; Gupta, Neeraj K.; Quraishi, M. A. (Royal Society of Chemistry, 2017)
The aims of the present work were to synthesise two functionalized graphene oxides, namely, diazo pyridine functionalized graphene oxide (DAZP-GO) and diamino pyridine functionalized graphene oxide (DAMP-GO), and to evaluate them as corrosion inhibitors on mild steel in 1 M hydrochloric acid. Electrochemical studies reveal that the inhibition efficiencies of both of the tested functionalized graphene oxides were enhanced with increasing concentration and the maximum inhibition efficiencies of 95.08% and 96.73% were obtained for DAMP-GO and DAZP-GO, respectively, at a concentration as low as 25 mg L-1. A potentiodynamic polarization study suggests that both DAZP-GO and DAMP-GO act as mixed type inhibitors with a slight cathodic predominance. The formation of a protective film on the mild steel surface was confirmed using scanning electron microscope, energy dispersive X-ray spectroscopy, atomic force microscopy and X-ray photoelectron spectroscopy techniques. Dynamic functional theory parameters such as EHOMO, ELUMO, energy band gap (ΔE), electronegativity (χ), hardness (η), softness (σ) and a fraction of electron transfer (ΔN) were calculated to support the experimental results.
Keywords: Pyridine; Graphene oxides; Steel; Corrosion